Ciclovías: una propuesta frente a la reducción de gases de efecto invernadero de la emisión de fuentes móviles en la ciudad de Iquitos 2016 - Davila Rodriguez, Cinthya Alessandra (2018)
I resolved the question: How to contribute to the reduction of greenhouse gases from the emission of mobile sources in the city of Iquitos? OBJECTIVE: Propose the Municipal ordinance that regulates the creation of the bike lane. In a qualitative-quantitative approach, with a descriptive research design, with a research universe of 467,817 inhabitants of the city of Iquitos, the sample was 96 citizens between 18 and 55 years of age based on stratified sampling with the survey technique. CONCLUSIONS: It is based on the environmental regulatory principles: a) Precaution. b) Prevention. c) Solidarity. Negative consequences caused by the absence of the Municipal ordinance that regulates the creation of the bike lane, directly impact the quality of the environment, the health of the population, affecting the fundamental rights of the person and environmental regulations. Positive impact of the proposal on the population: _ Effective awareness of the environment. - Start of a sustainable transportation system to fight pollution. Citizens' perception of the environmental situation in Iquitos: (81.3%) They perceive a deterioration in air quality. (49.0%) Perceives that smoke from motor vehicles is the greatest pollutant. (41.7%) Alternative to cycling. (64.5%) They have the need to implement a road cycle traffic plan that prevents the contamination of Iquitos.